Association Between Male Sex and Outcomes of Coronavirus Disease 2019 (COVID-19)—A Danish Nationwide, Register-based Study. (8th July 2020) - Kragholm, Kristian; Andersen, Mikkel Porsborg; Gerds, Thomas A; Butt, Jawad H; Østergaard, Lauge; Polcwiartek, Christoffer; Phelps, Matthew; Andersson, Charlotte; Gislason, Gunnar H; Torp-Pedersen, Christian; Køber, Lars; Schou, Morten; et al.
Abstract: Background and Objectives: Male sex has been associated with severe coronavirus disease 2019 (COVID-19) infection. We examined the association between male sex and severe COVID-19 infection and if an increased risk remains after adjustment for age and comorbidities. Methods: Nationwide register-based follow-up study of COVID-19 patients in Denmark until 16 May 2020. Average risk ratio comparing 30-day composite outcome of all-cause death, severe COVID-19 diagnosis or intensive care unit (ICU) admission for men versus women standardized to the age and comorbidity distribution of all patients were derived from multivariable Cox regression. Included covariates were age, hypertension, diagnoses including obesity, alcohol, sleep apnea, diabetes, chronic obstructive pulmonary disease, previous myocardial infarction (MI), ischemic heart disease (IHD), heart failure (HF), atrial fibrillation (AF), stroke, peripheral artery disease, cancer, liver, rheumatic, and chronic kidney disease (CKD). Results: Of 4842 COVID-19 patients, 2281 (47.1%) were men. Median age was 57 [25%–75% 43–73] for men versus 52 [38–71] for women (P < .001); however, octogenarians had equal sex distribution. Alcohol diagnosis, diabetes, hypertension, sleep apnea, prior MI and IHD (all P < .001) as well as AF, stroke, and HF (all P = .01) were more often seen in men, and so was CKD (P = .03). Obesity diagnosis (P < .001) were more often seen in women. Other comorbidity differences were insignificant (P > .05). The fully adjusted average risk ratio was 1.63 [95% CI, 1.44–1.84]. Conclusions: Men with COVID-19 infection have >50% higher risk of all-cause death, severe COVID-19 infection, or ICU admission than women. The excess risk was not explained by age and comorbidities. Abstract : Men with COVID-19 infection have a more than 50% higher risk of a 30-day composite outcome of all-cause death, severe COVID-19 infection, or ICU admission than women. This excess risk was not explained by age or underlying comorbid conditions.